Analisis pemanfaatan pelayanan pos pembinaan terpadu penyakit tidak menular dengan pendekatan teori Andersen dan Newman - Serlia Marthasari; Nurul Aryastuti; Samino Samino (Holistik Jurnal Kesehatan, 2023)
Background: Globally, the prevalence of hypertension in the world is (22 percent) of the total world population, in Indonesia, it is (34.11 percent), in Lampung Province is (15.10 percent), in Pringsewu Regency is (12.22 percent) and in the community health center technical implementing unit Gadingrejo (11.3 percent). A national action plan states that one of the strategies for controlling the non-communicable disease is through strengthening early detection and the active participation of the community through Integrated Healthcare Services for Non-Communicable DiseasesPurpose: To analyze of Integrated Healthcare Services for Non-Communicable Diseases using the Anderson and Newman theoretical approach.Method: The type of research used is using quantitative methods, and uses cross-sectional methods. The population of all target communities of Integrated Healthcare Services for Non-Communicable Diseases was productive age >15-59 years in the working area of community health center technical implementing unit Gadingrejo in 2022 amounted to 1,938 people with a sample of 268. Multivariate analysis used Structural Equation Modeling (SEM) analysis.Results: Finding a relationship between perceptions of integrated healthcare services for non-communicable diseases on family support (path coefficient -0.596 t statistic 2.898), perceptions of healthy behavior on perceptions of family support (path coefficient 0.582 t statistics 3.270), perceptions of integrated coaching post services on perceptions of health and illness (path coefficient 0.723 t statistic 6.174), perception of integrated coaching post service on integrated noncommunicable disease development post utilization (path coefficient 1.002 t statistic 11,654), perception of healthy behavior towards integrated non-communicable disease development post utilization (path coefficient -0.258 t statistic 3.226). There is no effect of the perception of healthy behavior on the perception of health and illness (path coefficient -0.028 t statistic 0.230), or the perception of family support on the perception of health and illness (path coefficient -0.045 t statistic 0.670). Based on the results of the study, it is hoped that health education will increase through visual, audio, and audiovisual media regarding the concept of health and illness, and healthy behavior in an effort to prevent hypertension and promote the benefits of integrated coaching posts to the community.Conclusion: The results of the test on the parameter coefficients between respondents’ perceptions have a significant effect on the Integrated Healthcare Services for Non-Communicable Diseases using the Anderson and Newman theoretical approach.Keywords: Utilization; Services; Integrated Healthcare Services for Non-Communicable DiseasesPendahuluan: Prevalensi hipertensi dunia secara global sebesar (22 persen) dari total penduduk dunia, di Indonesia sebesar (34,11 persen), di Propinsi Lampung sebesar (15,10 persen), di Kabupaten Pringsewu (12,22 persen) dan di UPT Puskesmas Gadingrejo (11,3 persen). Rencana Aksi Nasional P2PTM menyebutkan bahwa salah satu strategi penanggulangan PTM adalah melalui penguatan deteksi dini dan peran serta aktif masyarakat melalui posbindu PTM.Tujuan: Untuk menganalisis pemanfaatan layanan pos pembinaan terpadu penyakit tidak menular dengan pendekatan teori Andersen dan Newman.Metode: Jenis penelitian yang digunakan adalah menggunakan metode kuantitatif dengan menggunakan metode cross sectional. Populasi seluruh masyarakat sasaran posbindu PTM  usia produktif ≥ 15-59 tahun di wilayah kerja UPTD Puskesmas Gadingrejo tahun 2022 berjumlah 1.938 orang dengan sampel  sebanyak 268. Teknik analisis multivariat menggunakan analisis Structural Equation Modelling (SEM).Hasil: Didapatkan hubungan persepsi pelayanan posbindu terhadap persepsi dukungan keluarga  (path coefficient -0,596 t statistik 2,898), persepsi perilaku sehat terhadap persepsi dukungan keluarga (path coefficient 0,582 t statistik 3,270), persepsi pelayanan posbindu terhadap persepsi sehat sakit (path coefficient 0,723 t statistik 6,174), persepsi pelayanan posbindu terhadap pemanfaatan posbindu PTM (path coefficient 1,002 t statistik 11,654), persepsi perilaku sehat terhadap pemanfaatan posbindu PTM (path coefficient -0,258 t statistik 3,226). Tidak ada pengaruh persepsi perilaku sehat terhadap persepsi sehat sakit (path coefficient -0,028 t statistik 0,230), persepsi dukungan keluarga terhadap persepsi sehat sakit (path coefficient -0,045 t statistik 0,670). Berdasarkan hasil penelitian di harapkan peningkatan edukasi kesehatan melalui media visual, audio, audiovisual mengenai konsep sehat dan sakit, perilaku sehat dalam upaya pencegahan hipertensi, mempromosikan manfaat posbindu pada masyarakat.Simpulan: Hasil uji terhadap koefisien parameter antara persepsi pemanfaatan layanan posbindu berpengaruh dengan Pos Pembinaan Terpadu Penyakit Tidak Menular (Posbindu PTM) dengan pendekatan teori Andersen dan Newman.